Laboratory experiments for crude oil removal from water surface using hydrophobic nano-silica as sorbent - Knapik, Ewa; Stopa, Jerzy (My University, 2014)
Nanomaterials have a great potential for the possible oil spill cleanup due to their unique wettability characteristics and large surface area. This work reports investigations on oil sorption behavior of a commercially available hydrophobic nano-silica when tested with a light paraffinic crude oil and a heavy aromatic crude oil. Sorption experiments were carried out in batch sorption system under static and dynamic conditions. Influence of mass of sorbent, sorption time, temperature and pH value of water on sorption capacity were tested and compared to find an optimal operational conditions for adsorption process. Nanopowder exhibited high selectivity for absorbing oil from water; a removal efficiency found by gravimetric method was high as 96% to 99%. The sorption capacity inereases with the inerease of sorption time and mass of sorbent. Nano-silica powder was found to be effective sorbent material as compared to widely used synthetic fibers.
AGH Drilling, Oil, Gas
Keywords: oil sorbent; hydrophobicity; nano-silica; batch adsorption